Evaluation of recent ridership increases - Stanley, Robert G. (Research results digest (Transit Cooperative Research Program), 2005)
"This TCRP digest is the final report of Task 51 for Project J-6, 'Quick Response for Special Needs.' ... The digest was prepared by Robert G. Stanley and Robert Hyman of Cambridge Systematics, Inc."